Genetic Differentiation of Bipolaris spp. based on Random Amplified Polymorphic DNA markers - K.D. SRIVASTAVA and RENU, M. JAHANI, RASHMI AGGARWAL*, (Indian Phytopathology, 2008)
Seventeen Indian isolates of Bipolaris spp. which included 12 isolates of Bipolaris sorokiniana, two isolates each of B. specifera and B. tetramera and one isolate of B. maydis were taken up for identification of genetic markers and to provide a protocol for identification and characterization of isolates using Randomly Amplified Polymorphic DNA (RAPD) technique. The genomic DNA was compared using 40 random decamer primers (Operon Technologies Inc., U.S.A.) that generated 554 bands; out of which 549 were polymorphic products. Genetic similarities of RAPD profiles were estimated on the basis of Jaccard’s coefficient. The similarity index values ranged from 0.474 to 0.906 indicating the presence of wide range of genetic diversity. These similarity coefficients were subjected to Unweighted Pair Group Method on Arithmetic Averages (UPGMA) using paired matrix values. The dendrogram generated consisted of 2 major clusters, one having all isolates of B. sorokiniana, and other cluster having isolates of B. specifera, B. tetramera and B. maydis which were further distinguishable from each other by falling into different sub-groups. The banding pattern of different isolates can also be used as reference for further comparisons.